Implementasi Autentikasi Mode Multi-Auth Pada Jaringan Local Area Network Berbasis Kabel Menggunakan Protokol IEEE 802.1X Dan Radius Server - Andre Rizal Sinaga; Rakhmadani Primananda; Primantara Hari Trisnawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In computer network area, authentication, integrity, authentication time and scalability are the main problems to keep the network safe, faster and stable. The working administrator must have a complete network management, scalability and security account, so that organization or company data can be kept confidential and can maintain the integrity of the data. There are many implementations that have been done with different authentication methods used in the IEEE 802.1X standard one of which uses EAP-PEAP which is quite easy to implement and has a pretty good level of security. In addition to security, time in authentication to the network is important and in realizing a secure network environment still needs to measure in terms of network implementation costs. The multi-auth mode of implementing it costs cheaper because the physical port can be extended with a hub but functions the same as single-host mode where each MAC address must be authenticated based on the credentials sent by the user. The result of the research shows that the integrity of the delivery of data credentials sent can be maintained due to the successful implementation of the encryption RSA and hashing SHA1 algorithm in the system and the authentication time is measured from two parameters that are